Cemented versus Cementless Total Hip Arthroplasty in Paget's Disease of Bone: A Systematic Review - Hurley, Eoghan T.; Cashman, James; Synnott, Keith A.; O'Byrne, John M.; Lyons, Frank G. (The Journal of Hip Surgery, 2017)
The purpose of this study is to systematically review the clinical evidence for the use of cemented and cementless total hip arthroplasty (THA) in Paget's disease of bone (PDB), and to ascertain whether any difference exists in clinical outcomes between the two implant types. MEDLINE, EMBASE, and the Cochrane Library databases were searched in accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. The quality of the studies was assessed using the methodological index for nonrandomized studies (MINORS) checklist. The reported clinical outcomes were evaluated using risk ratio (RR) with a p < 0.05 considered as statistically significant. Thirteen clinical studies with 444 primary THAs were included in this review. Cementless THA resulted in lower rates of aseptic loosening and lower rates of revision due to aseptic loosening (p < 0.05), but there was no overall statistically significant increase in the incidence of revision in the cemented THAs (p = 0.21). The postoperative Harris hip score was similar between both the groups. Also, the presence of heterotrophic ossification was similar in both the groups. Functional outcomes and survivorship were equivalent using either cementless or cemented components, with a similar rate of overall revisions. However, cementless components resulted in a decreased incidence of aseptic loosening and revision due to aseptic loosening. The current literature consists of a low level of evidence, level IV, which limits the conclusion of this study.
Keywords: arthroplasty; hip; Paget's disease of bone; systematic review